PENEGUHAN DAN PENGUATAN KEMPUAN SOFT SKIL DEMI MENUNJANG EKONOMI DAN PENDIDIKAN ISLAM YANG BERKEMAJUAN - Fauzi, Abi; Vernando, Vellix; Handayani, Indrastuti; Alfarobi, Thufail; Baskoro, Ilham Fajar; Sari, Indri Putriana Dewita; Yulyani, Arti; Kholifah, Alista Pristantika Nur; Lestari, Vina Ayu; Amir, Paisal; Fatur, Abdul Hasan; Lismawati, Lismawati (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Seeing that there are several problems that occur in the North Cipete sub-district. Among other things, there are problems with people's understanding regarding online buying and selling, the lack of interactive media and methods for learning the Qur'an, the lack of interest in learning, especially in Islamic Religious Education, Arabic Language Education, and Sharia Banking Economics. Thus, the first step in starting this KKS activity program, we coordinated with several parties such as DKM (Mosque Prosperity Council), PKK Mother, Karang Taruna, and educational institutions (TPQ Al-Istiqomah), as well as residents of Cipete Utara Subdistrict RT.07 RW. 02.We hope that through the efforts of this Social Work Lecture (KKS) activity carried out by FAI UHAMKA group 2 students at Muhammadiyah University, Prof. Dr. HAMKA with its spirit of collaboration, knowledge and high dedication can become an agent of change for the people of Cipete Utara RT. 07/RW.02 in helping community empowerment and developing personal potential optimally. Apart from that, the Social Work Lecture (KKS) program is not only a source of knowledge, but also a source of experience for students in social activities and to strengthen Islamic brotherhood.The activity strategy in implementing the Social Work Lecture (KKS) is carried out through an active approach, namely mingling with the community and through workshop presentation methods regarding digital marketing and the introduction of sharia banking, as well as PAI, PBA and PS training materials, learning at the TPQ Al institution -Istiqomah with story telling, learning while playing, learning with songs and movements, question and answer, and using digital media to achieve innovative and progressive learning goals.In implementing this social work lecture, the focus is on strengthening soft skills through empowerment and teaching to residents of the North Cipete RT.07/RW.02 community. As said by the chief executive of KKS activities, the aim of implementing this activity and training program is so that people are able to do business through digital and market products online, one of which is through shopefood as business support